A low-roughness PET film and its preparation process
By combining the inorganic filler with functional polymers, a PET film with ABA three-layer composite structure is solved, and the problem of insufficient surface roughness and viscosity resistance of the polyester film is achieved, high dispersion and stability are achieved, and the toughness of the film is improved. and heat resistance.
Patent Information
- Application Number
- CN202411013133.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing polyester films still have shortcomings in surface roughness and anti-viscosity, and nano- or micro-scale inorganic particles are prone to agglomeration, resulting in a decrease in processing performance, and small molecules organic components in the coating liquid are easily precipitated.
By combining the inorganic filler with the functional polymer, a PET film with a three-layer composite structure is formed. The good compatibility between the functional polymer and PET is used to improve the dispersion of inorganic particles, and the bromine and inorganic in the polymer are used to achieve the polymer. The amino group in the filler reacts to form a brush-like polymer, improving the stability of surface energy.
It effectively reduces the surface roughness of the PET film, improves the toughness and heat resistance of the film, enhances the dispersion and processing performance of inorganic particles, and is suitable for high-performance applications such as release films.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester films, in particular to a low-roughness PET film and a preparation process thereof. Background Art
[0002] At present, the polyester film used on the market is usually polyethylene terephthalate (PET), which is a colorless, transparent, glossy film with good mechanical properties, high hardness and toughness, excellent puncture resistance and friction resistance. Therefore, it is used in many fields such as electrical insulation film, capacitor film, release film, composite current collector film, polarizer protective film, packaging film, etc.
[0003] When used as a release film or protective film, the PET film needs to have a low surface roughness, a certain degree of anti-stickiness and surface smoothness. In response to such high-performance requirements, the current modification technology solutions for polyester films include adding nano-scale or micro-scale inorganic particles, such as silicon dioxide, calcium carbonate, etc., to its surface to reduce surface roughness; or coating the film surface with a coating containing micro-scale particles to improve the surface tension of the film. However, the current technical solutions for polyester films are still insufficient. The addition of inorganic particles requires controlling their size and addition amount, and the resulting surface roughness still cannot meet Ra≤15nm, and the inorganic particles are prone to agglomeration, resulting in decreased processing performance; and although the coating formed by coating can improve the surface tension, the coating liquid usually contains small molecular organic components, which are also prone to precipitation risks during subsequent processing. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention compounds inorganic fillers with functional polymers and adds them to the surface PET to form a PET film with an ABA three-layer composite structure. The inorganic particles on the surface of the film have good dispersion, high stability, and the surface roughness is effectively reduced.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A low-roughness PET film, the PET film is co-extruded with an ABA three-layer structure and biaxially stretched, the A-layer raw material comprises 70 to 90 parts of PET chips and 10 to 30 parts of special masterbatch; the B-layer raw material is PET chips;
[0007] The special masterbatch is prepared from 20-40wt% KH550 modified inorganic filler and 60-80wt% functional polymer. The functional polymer is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30-90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder to obtain the special masterbatch.
[0008] The functional polymer is a semi-aromatic polyamide prepared from aromatic dibasic acid, aliphatic dibasic acid, a siloxane-containing diamine monomer, aliphatic diamine and a hydroxyl-containing end-capping agent.
[0009] Furthermore, the KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal mass of KH550, stirring at 50°C for 24 hours, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide.
[0010] Furthermore, the aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid, and malonic acid; and the aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid.
[0011] Furthermore, the siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400 to 1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine.
[0012] Furthermore, the hydroxyl-containing capping agent is ethanolamine or o-hydroxyaniline.
[0013] Furthermore, the molar ratio of the aromatic dibasic acid, aliphatic dibasic acid, siloxane-containing diamine monomer, and aliphatic diamine is 3:2:1:4; and the amount of the hydroxyl-containing end-capping agent is 0.1 to 5 wt % of the total mass of the above four monomers.
[0014] Furthermore, the raw material usage ratio of the ABA three-layer structure is A layer: B layer: A layer = 10-20: 60-80: 10-20.
[0015] The present invention further provides a process for preparing the low-roughness PET film as described above, comprising the following steps:
[0016] S1. Mix the measured PET chips and special masterbatch and send them into the auxiliary extruder; put the pure PET chips into the crystallizer, pre-crystallize at 120-140°C for 15 minutes, and then send them into the drying tower for drying, and then send them into the main extruder after drying;
[0017] S2, adjust the temperature of the auxiliary extruder to 265-290°C, the temperature of the main extruder to 255-270°C, after melting, measure, extrude and filter;
[0018] S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process;
[0019] S4, preheating the cast sheet at 65-90°C, and longitudinally stretching it 3-3.5 times at 90-110°C to obtain a longitudinally stretched sheet; then preheating it at 90-120°C, and transversely stretching it 3.5-4 times at 100-130°C; after stretching, heat setting, cooling, pulling and winding are performed to obtain the sheet.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) The present application prepares a semi-aromatic polyamide as a functional polymer and an inorganic filler to form a special masterbatch. The inorganic filler is a silica particle modified by a silane coupling agent, and an amino group is introduced on the surface of the inorganic particle. The functional polymer is a semi-aromatic polyamide, which is formed by reacting aromatic dibasic acid, aliphatic dibasic acid (2-bromoterephthalic acid or 5-bromoisophthalic acid), a siloxane diamine monomer, an aliphatic diamine and a hydroxyl-containing end-capping agent as raw materials. The silica particles are grafted onto the polymer chain to form a brush-like polymer by reacting the bromine in the polymer with the amino group in the inorganic filler. The terminal hydroxyl group can also produce a hydrogen bond effect with the amino group, promoting the interaction and reaction between molecules, thereby improving the dispersibility of the inorganic particles. The functional polymer is mixed with PET to have good compatibility, which better solves the technical problem that nanomaterials agglomerate and are difficult to disperse in polyester materials. At the same time, the inorganic particles compounded with the functional polymer are also difficult to precipitate from the surface of the film, which improves the stability of the surface energy of the film surface during processing and use.
[0022] 2) Semi-aromatic polyamide has excellent mechanical properties and heat resistance. Introducing it into PET film can effectively improve the heat resistance of the material; combining with inorganic fillers can effectively improve the impact strength of the film. PET mixed with special masterbatch is used as the outer layer of the intermediate core layer formed by pure PET slices, and synergistically acts with the intermediate core layer to improve the toughness of the film; the film surface is smooth and has low roughness, which is very suitable for use as a release film such as the base film of MLCC release film. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0025] Example: A low roughness PET film
[0026] The ABA three-layer structure is co-extruded and biaxially stretched. The A layer raw material includes 70-90 parts of PET chips and 10-30 parts of special masterbatch; the B layer raw material is PET chips; the preparation process is as follows:
[0027] S1. Mix the measured PET chips and special masterbatch and send them into the auxiliary extruder; put the pure PET chips into the crystallizer, pre-crystallize at 120-140°C for 15 minutes, and then send them into the drying tower for drying, and then send them into the main extruder after drying;
[0028] S2, adjust the temperature of the auxiliary extruder to 265-290°C, the temperature of the main extruder to 255-270°C, after melting, measure, extrude and filter;
[0029] S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process;
[0030] S4, preheating the cast sheet at 65-90°C, and longitudinally stretching it 3-3.5 times at 90-110°C to obtain a longitudinally stretched sheet; then preheating it at 90-120°C, and transversely stretching it 3.5-4 times at 100-130°C; after stretching, heat setting, cooling, pulling and winding are performed to obtain the sheet.
[0031] Embodiment 1:
[0032] An ABA three-layer structure PET film is prepared according to the above process, wherein the raw material of layer A includes 70 parts of PET chips and 30 parts of special masterbatch; the raw material of layer B is PET chips; and the raw material usage ratio is layer A: layer B: layer A = 10:80:10.
[0033] The special masterbatch is prepared from 20wt% KH550 modified inorganic filler and 80wt% functional polymer. The functional polymer is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30 to 90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder to obtain the special masterbatch.
[0034] Furthermore, the KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal mass of KH550, stirring at 50°C for 24 hours, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide.
[0035] The functional polymer is a semi-aromatic polyamide prepared from aromatic dibasic acid, aliphatic dibasic acid, a siloxane-containing diamine monomer, aliphatic diamine and a capping agent.
[0036] Specifically, the molar ratio of the aromatic dibasic acid, the aliphatic dibasic acid, the siloxane-containing diamine monomer, and the aliphatic diamine is 3:2:1:4; and the amount of the hydroxyl-containing end-capping agent is 1 wt% of the total mass of the above four types of monomers.
[0037] In an optional embodiment, the aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid, and malonic acid; the aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid. The siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400 to 1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine.
[0038] In this embodiment, 2-bromoterephthalic acid, succinic acid, aminopropyl-terminated polydimethylsiloxane (1000), and ethylenediamine are used as raw materials, and the raw materials are weighed according to a molar ratio of 3:2:1:4. 2-bromoterephthalic acid and succinic acid are pre-mixed and dissolved in toluene, and nitrogen is introduced. Then, hexamethylenediamine is added dropwise under mechanical stirring, and refluxed for 3 hours after the addition is completed; then, a toluene dilution containing aminopropyl-terminated polydimethylsiloxane is added dropwise, and refluxed for 2 hours after the addition is completed; finally, ethanolamine is added to react for 1-2 hours, and the resulting mixture is precipitated and washed with acetone and water, and dried to obtain a functional polymer.
[0039] Embodiment 2:
[0040] The same as Example 1, except that the ratio of raw materials used is layer A: layer B: layer A = 20:60:20.
[0041] Embodiment 3:
[0042] The same as Example 1, except that the raw material of layer A includes 80 parts of PET chips and 20 parts of special masterbatch; the raw material of layer B is PET chips; and the raw material usage ratio is layer A: layer B: layer A = 20:60:20.
[0043] Embodiment 4:
[0044] The same as Example 1, except that the raw material of layer A includes 90 parts of PET chips and 10 parts of special masterbatch; the raw material of layer B is PET chips; and the raw material usage ratio is layer A: layer B: layer A = 20:60:20.
[0045] Comparative Example:
[0046] Same as Example 1, except that the special masterbatch is obtained by directly extruding and granulating 20 wt % of silicon dioxide and 80 wt % of functional polymer.
[0047] The relevant properties of the PET films obtained in the above examples and comparative examples were examined, and the results are recorded in Table 1.
[0048] Table 1
[0049] Example 1 Example 2 Example 3 Example 4 Comparative Example Pure PET film Thermal shrinkage MD / TD% 1.21 / 0.35 1.03 / 0.12 1.14 / 0.17 1.26 / 0.20 1.52 / 0.42 1.93 / 0.61 Surface roughness Ra(nm) 12 9 10 13 18 27
[0050] Observe Table 1, compare the comparative example with the pure PET film, and directly extrude and granulate the inorganic filler silica and the functional polymer to obtain the special masterbatch, which improves the performance of the PET film to a certain extent, but there is still considerable room for improvement. The surface roughness (Ra) of the PET film obtained in this application can reach 9nm, and the other embodiments can also achieve less than 15nm, achieving a low surface roughness polyester film.
[0051] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A low roughness PET film, characterized in that: The PET film is co-extruded with an ABA three-layer structure and biaxially stretched. The raw material of the A layer includes 70-90 parts of PET chips and 10-30 parts of special masterbatch; the raw material of the B layer is PET chips; The special masterbatch is prepared from 20-40wt% KH550 modified inorganic filler and 60-80wt% functional polymer. The functional polymer is dissolved in a mixed solvent of toluene and ethanol in a reaction bottle, and a catalyst LHMDS is added and mixed evenly. The KH550 modified inorganic filler is evenly dispersed in ethanol and then added to the reaction bottle, stirred at room temperature for 30-90 minutes, then quenched with sodium bicarbonate and filtered, the filter cake is washed with acetone and water and then dried, and extruded and granulated by an extruder to obtain the special masterbatch. The functional polymer is a semi-aromatic polyamide prepared from an aromatic dibasic acid, an aliphatic dibasic acid, a siloxane-containing diamine monomer, an aliphatic diamine, and a hydroxyl-containing end-capping agent; the aromatic dibasic acid is selected from 2-bromoterephthalic acid or 5-bromoisophthalic acid; The KH550 modified inorganic filler is obtained by placing a certain amount of inorganic particles in a 5wt% potassium hydroxide solution for activation treatment, then redispersing the treated inorganic particles in deionized water and adding an equal amount of KH550, stirring at 50°C for 24h, filtering, washing, drying and grinding; the inorganic particles are silicon dioxide; The siloxane-containing diamine monomer is aminopropyl-terminated polydimethylsiloxane with a molecular weight of 400-1000; the aliphatic diamine is selected from one of 1,2-diamino-2-methylpropane, 2,5-dimethyl-2,5-hexanediamine, dimethylpropylenediamine, hexamethylenediamine, and ethylenediamine; The hydroxyl-containing end-capping agent is ethanolamine or o-hydroxyaniline.
2. The low-roughness PET film according to claim 1, characterized in that The aliphatic dibasic acid is selected from one of succinic acid, adipic acid, pimelic acid, glutaric acid and malonic acid.
3. The low-roughness PET film according to claim 1, characterized in that The molar ratio of the aromatic dibasic acid, the aliphatic dibasic acid, the siloxane-containing diamine monomer, and the aliphatic diamine is 3:2:1:4; the amount of the hydroxyl-containing end-capping agent is 0.1-5wt% of the total mass of the above four types of monomers.
4. The low-roughness PET film according to claim 1, characterized in that The raw material usage ratio of the ABA three-layer structure is A layer: B layer: A layer = 10~20: 60~80: 10~20.
5. A process for preparing a low-roughness PET film as described in any one of claims 1 to 4, characterized in that: The steps include: S1. Mix the measured PET slices and special masterbatch and send them into the auxiliary extruder; put the pure PET slices into the crystallizer, pre-crystallize at 120-140°C for 15 minutes, and then send them into the drying tower for drying, and then send them into the main extruder after drying; S2, adjust the temperature of the auxiliary extruder to 265~290℃, the temperature of the main extruder to 255~270℃, after melting, measure, extrude and filter; S3, using the materials extruded by the auxiliary extruder as the upper and lower surface layers, and the materials extruded by the main extruder as the middle core layer, and making an ABA three-layer composite casting sheet through a multi-layer co-extrusion process; S4, preheat the cast sheet at 65-90°C, and longitudinally stretch it 3-3.5 times at 90-110°C to obtain a longitudinally stretched sheet; then preheat it at 90-120°C, and transversely stretch it 3.5-4 times at 100-130°C; after stretching, heat-set it, and then cool it, pull it and roll it up to obtain the sheet.
Citation Information
Patent Citations
Low-roughness release film base film and preparation method thereof
CN113524848A
Modified polyamide separation membrane and preparation method thereof
CN114768555A
Co-polyester packaging resins prepared without solid-state polymerization, a method for processing the co-polyester resins with reduced viscosity change and containers and other articles prepared by the process
US20070248778A1